Retrospective review of pediatric patients with acute lymphoblastic leukemia: A single center experience - Khalid Safoorah; Moiz Bushra; Adil Salman; Khurshid Mohammad (Wolters Kluwer Medknow Publications, 2010)
Objective: We reviewed the clinical details and treatment outcome of children with newly diagnosed acute lymphoblastic leukemia (ALL) to determine the significance of already established prognostic factors in our patients. Setting: A tertiary care hospital in Karachi, Pakistan. Study Design: This is a retrospective study. Materials and Methods: Children diagnosed with ALL were evaluated over a period of 17 years (January 1, 1989 to December 31, 2006). Data was collected by reviewing the medical records of the patients and the prognostic factors analyzed by us include age, gender, white blood cell count, central nervous system and mediastinal involvement at presentation, morphology and immunophenotype of the blast cells, and response to induction therapy. Results: There were 46 patients diagnosed during the study period and on regular follow-up. Forty five (97.8%) of these were in complete remission after 28 days of induction therapy. Thirty patients (65.2%) were alive and doing well at the time of study. Of these 30 patients, 26 (86.6%) remained relapse free while only four (13.3%) had relapsed. The remaining 16 patients (34.7%) did not survive including 11 (68.7%) who had a relapse. Only significant variables in terms of prognosis were age and ALL phenotype with a P value 0.04 and 0.03 respectively. Conclusion: We found that ALL is a frequent childhood hematological malignancy in our setting and is more prevalent in males and children less than ten years of age. Age and leukemia phenotype emerged as the important prognostic factors in pediatric ALL in our patients.